A Framework for Analyzing the Ethics of Disclosing Genetic Research Findings. Issue 2 (2014) - Eckstein, Lisa; Garrett, Jeremy R.; Berkman, Benjamin E.
Abstract : Over the past decade, there has been an extensive debate about whether researchers have an obligation to disclose genetic research findings, including primary and secondary findings. There appears to be an emerging (but disputed) view that researchers have some obligation to disclose some genetic findings to some research participants. The contours of this obligation, however, remain unclear. As this paper will explore, much of this confusion is definitional or conceptual in nature. The extent of a researcher's obligation to return secondary and other research findings is often limited by reference to terms and concepts like "incidental, " "analytic validity, " "clinical validity, " "clinical relevance, " "clinical utility, " "clinical significance, " "actionability, " and "desirability." These terms are used in different ways by different writers to describe obligations in different sorts of cases.